Answer:
The statement is not true. There is an error in the following step:
[tex]\frac{r^{k} * r^{k} }{r^{(k-1)} } = \frac{1 * 1}{1}[/tex]
Step-by-step explanation:
Here is the complete proof:
[tex]r^{k + 1} = r^{k + k - (k - 1)}[/tex] (because k + k - (k - 1) = k + 1)
[tex]= \frac{r^{k} * r^{k} }{r^{(k-1)} }[/tex] (By laws of exponent)
[tex]= \frac{r^{k} * r^{k} }{r^{k} * r^{-1} } }[/tex]
[tex]= \frac{r^{k} * r^{k} * r^{1} }{r^{k}} }[/tex] (Since the power of r is a negative integer i.e. -1 it will shift to the numerator)
[tex]= r^{k} * r^{1}[/tex] (We get this equation after canceling out the similar terms in numerator and denominator in previous step)
[tex]= r^{k + 1} \neq 1[/tex] (Provided r > 1 or r < -1)